2022
DOI: 10.1111/1462-2920.15872
|View full text |Cite
|
Sign up to set email alerts
|

Damming river shapes distinct patterns and processes of planktonic bacterial and microeukaryotic communities

Abstract: Planktonic bacterial and microeukaryotic communities play important roles in biogeochemical cycles, but their biogeographic patterns and community assembly processes in large damming rivers still remain unclear. In this study, 16S rRNA and 18S rRNA coding genes were used for sample sequencing analysis of planktonic bacterial and microeukaryotic communities in the upper Yangtze River. The upper Yangtze River was divided into damaffected zones and river zones based on the influence of dams. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Dams, especially cascade hydropower dams, are serious anthropogenic disturbances in rivers that may affect the biogeographical patterns of the planktonic microbial communities (Grantham et al, 2014; Han et al, 2018). A previous study suggested that operation of dams had a considerable impact on the biogeographical patterns of bacteria and microeukaryote in the upper Yangtze River (Lu et al, 2022). This is likely to be because cascade hydropower dams impact connectivity among river regions, resulting in spatial segregation of microbial communities in different reservoir areas (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Dams, especially cascade hydropower dams, are serious anthropogenic disturbances in rivers that may affect the biogeographical patterns of the planktonic microbial communities (Grantham et al, 2014; Han et al, 2018). A previous study suggested that operation of dams had a considerable impact on the biogeographical patterns of bacteria and microeukaryote in the upper Yangtze River (Lu et al, 2022). This is likely to be because cascade hydropower dams impact connectivity among river regions, resulting in spatial segregation of microbial communities in different reservoir areas (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of various anthropogenic factors on natural habitats is well documented. With the amplified impact of anthropogenic activities, various naturally occurring ecological niches have been destroyed (Lu et al, 2022). The deterioration of water quality and its impact on deterioration in the river Ganga ecology is noteworthy (Das et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The difference of assembly mechanism between prokaryotic and microeukaryotic community in SYBH is consistent with previous research on protist and bacteria in global surface waters (Logares et al, 2020) and upwelling system (Sun et al, 2022), but contradict with that in East China Sea's euphotic zone where protist community is mainly structured by selection processes (Wu et al, 2018). Such inconsistency has been discussed in several studies on microbiomes across different ecosystems (Xue et al, 2018;Xiong et al, 2021;Lu et al, 2022;Sun et al, 2022), supporting that the combined effect of species, straits, habitat type, spatiotemporal scale and environmental gradient determine the relative contribution of determinism and stochasticity in shaping the microbial landscape (Chase and Myers, 2011;Hanson et al, 2012;Morrison-Whittle and Goddard, 2015).…”
Section: Distinct Patterns and Drivers Of Microeukaryotic And Prokary...mentioning
confidence: 93%
“…Although amplicon libraries for metabarcoding of prokaryotes and eukaryotes have to be prepared separately due to the distinct nucleotide characters, they form microbial assemblage in natural waters and play roles together in ecological processes such a microbial food web. Recently, increasing attention has been paid to joint analysis of microbial prokaryotic and eukaryotic plankton in aquatic ecosystems (Jiang et al, 2018;Wu et al, 2020;Lu et al, 2022;Sun et al, 2022), revealing that the distribution patterns and assembly mechanisms are distinct between domains, and cross-domain interaction plays an important role in shaping the plankton community, even overriding abiotic factor in some cases. Which process contributes more to the community assembly?…”
Section: Introductionmentioning
confidence: 99%